Harmonic aggregation techniques for power quality assessment a standard framework - Share Pasand, Mohammad Mahdy; Rahmatian, Zahra (International Journal of Engineering and Technology, 2014)
A review on the existing methods for aggregation of harmonic currents including recommended method used in IEC 61000-3-6 standard is performed and different approaches are compared. Main advantages of each method are outlined and simulation studies are performed to assess each method. A simple technique is proposed to base future research and standardization on. The proposed technique is simple, reliable and realistic though requires experimental data to derive parameters. Keywords: Electromagnetic Compatibility; Harmonic Distortion; Harmonic Aggregation; Power Quality; Current Harmonics.